2019
DOI: 10.1128/jvi.00996-19
|View full text |Cite
|
Sign up to set email alerts
|

Dengue Virus M Protein Promotes NLRP3 Inflammasome Activation To Induce Vascular Leakage in Mice

Abstract: Dengue virus (DENV) infection causes serious clinical symptoms, including dengue hemorrhagic fever (DHF) and dengue shock syndrome (DSS). Vascular permeability change is the main feature of the diseases, and the abnormal expression of proinflammatory cytokines is the important cause of vascular permeability change. However, the mechanism underlying vascular permeability induced by DENV has not been fully elucidated. Here, we reveal a distinct mechanism by which DENV infection promotes NLRP3 inflammasome activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
56
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 49 publications
2
56
1
Order By: Relevance
“…Furthermore, NS2A was shown to colocalize with NLRP3. Recently, it has been demonstrated that DENV-2 envelope protein domain III and M proteins also trigger NLRP3 activation (34,35). Furthermore, studies have reported that some RNA viruses (Chikungunya and Zika) activate the AIM2-specific inflammasome (70,71).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, NS2A was shown to colocalize with NLRP3. Recently, it has been demonstrated that DENV-2 envelope protein domain III and M proteins also trigger NLRP3 activation (34,35). Furthermore, studies have reported that some RNA viruses (Chikungunya and Zika) activate the AIM2-specific inflammasome (70,71).…”
Section: Discussionmentioning
confidence: 99%
“…DENV NS2A hydrophobic regions have demonstrated to have strong interactions with several Eukariothic model membrane systems (33). Although several studies have provided some clues regarding the role of different molecules of DENV that trigger the inflammatory process (34,35), the mechanism of NLRP3 activation is not fully understood. In the current study, we have attempted to shed more light on the role of the putative viroporins NS2B and NS2A in the regulation of inflammasome activation.…”
Section: Introductionmentioning
confidence: 99%
“…The roles of SARS-CoV-2 proteins in regulating the secretion of mature IL-1β were assessed in a reconstructed NLRP3 in ammasome system as described previously 15 . HEK293T cells were cotransfected with plasmids encoding the three components (NLRP3, ASC, and pro-Casp-1) of the NLRP3 in ammasome and the substrate pro-IL-1β to generate a NLRP3 in ammasome system.…”
Section: Resultsmentioning
confidence: 99%
“…In ammasomes are named according to different sensing proteins, and there are mainly four types: NLRP1, NLRP3, NLRC4 and AIM2 13 . Among them, the NLRP3 in ammasome is closely related to RNA virus infection 14,15 , which consists of a sensor protein (NLR family PYRIN domain containing-3, NLRP3), an adaptor protein (Apoptosis-associated speck-like protein containing a caspase recruitment domain, ASC), and an effector protein (Caspase-1, Casp-1) 16 . NLRP3 protein contains three domains: Pyrin domain (PYD), Nucleotidebinding domain (NBD), and Leucine-rich repeat domain (LRR) 15 .…”
mentioning
confidence: 99%
See 1 more Smart Citation